Combining Hydrophilic and Hydrophobic Materials in 3D Printing for Fabricating Microfluidic Devices with Spatial Wettability. Issue 9 (21st July 2021) - Männel, Max J.; Weigel, Niclas; Hauck, Nicolas; Heida, Thomas; Thiele, Julian
Abstract: The fabrication of microfluidic flow cells via projection micro‐stereolithography (PμSL) has excited researchers in recent years. However, due to the inherent process properties of most commercial PμSL, microfluidic devices are fabricated in a monolithic fashion with uniform material properties across a flow cell. Yet, the large surface‐to‐volume ratio in microfluidics demands to tailor microchannel surface properties—particularly in planar microchannel arrangements—with spatial control and micron‐scale resolution to form a desired flow profile, e.g., emulsion droplets. Here, the fabrication of planar microfluidic devices by PμSLbased 3D printing with spatial control over surface properties is presented. For that, homemade photopolymer formulations being either hydrophilic or hydrophobic are designed. Adding acrylic acid to a resin containing poly(ethylene glycol) diacrylate lowers the contact angle down to 0° against water creating a superhydrophilic surface. By utilizing 1 H, 1 H, 2 H, 2 H ‐perfluorodecyl acrylate, a photopolymer formulation allowing for 3D‐printing a hydrophobic microchannel surface with a contact angle >120° against water is obtained. Combining these two materials, microfluidic flow cells with spatially defined wettability are 3D‐printed for emulsion formation. Finally, the resin vat of the commercial PμSL printer is switched during the printing process for fabricating multimaterial geometries, as exemplarily applied for realizing a hydrophobic‐hydrophilic‐hydrophobic device for forming O/W/O double emulsions. Abstract : The fabrication of planar microfluidic devices with micron‐scale features by additive manufacturing is described, exhibiting spatially controlled surface properties. For that, homemade resins with either hydrophilic or hydrophobic properties are designed and processed in a step‐by‐step fashion to yield flow cells with defined wettability pattern for single‐ and double‐emulsion formation.